Identification of DNA methylation associated enrichment pathways in adults with non-specific chronic low back pain. (November 2020) - Aroke, Edwin N; Overstreet, Demario S; Penn, Terence M; Crossman, David K; Jackson, Pamela; Tollefsbol, Trygve O; Quinn, Tammie L; Yi, Nengjun; Goodin, Burel R
Chronic low back pain (cLBP) that cannot be attributable to a specific pathoanatomical change is associated with high personal and societal costs. Still, the underlying mechanism that causes and sustains such a phenotype is largely unknown. Emerging evidence suggests that epigenetic changes play a role in chronic pain conditions. Using reduced representation bisulfite sequencing (RRBS), we evaluated DNA methylation profiles of adults with non-specific cLBP (n = 50) and pain-free controls (n = 48). We identified 28, 325 hypermethylated and 36, 936 hypomethylated CpG sites (p < 0.05). After correcting for multiple testing, we identified 159 DMRs (q < 0.01and methylation difference > 10%), the majority of which were located in CpG island (50%) and promoter regions (48%) on the associated genes. The genes associated with the differentially methylated regions were highly enriched in biological processes that have previously been implicated in immune signaling, endochondral ossification, and G-protein coupled transmissions. Our findings support inflammatory alterations and the role of bone maturation in cLBP. This study suggests that epigenetic regulation has an important role in the pathophysiology of non-specific cLBP and a basis for future studies in biomarker development and targeted interventions.